PREDIKSI PERUBAHAN PENGGUNAAN LAHAN SAWAH DI WILAYAH HILIR DAS BILA TAHUN 2036 - Hidayat, Arnur; Asra, Reza; Thamrin, Nining Triani; Mubarak, Husnul (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
The use of rice fields as non-agricultural land if allowed to continue, it is not impossible that agricultural land will become increasingly narrow, agricultural production will decline in the long term and Indonesia will experience a food deficit, so it is important to predict rice fields so that it becomes a consideration for the government and other related agencies in determining policies regarding land use planning in an area to support land resource management and sustainable regional development planning. This study aims to analyze the driving factors of rice field changes based on Geographic Information Systems (GIS) and to determine the projection of rice field changes using the Ca-Markov 2036 model. This study is based on Geographic Information Systems (GIS), a system designed to capture, store, manipulate, analyze, organize and display all types of geographic data. The process of processing driving factors data starts from the weighting classification process, fuzzy analysis to produce output that is a reference for the CA-Markov process. Ca-Markov Method Using Idrisi Selva. from the results of the study of Land Use Changes in 2024-2036 in the downstream area of ​​the Bila watershed, it shows that the land changes that increased on the land were Rice Fields covering an area of ​​975,247 ha, Plantations covering an area of ​​594,523, Settlements covering an area of ​​1641,144 ha, while the land that experienced a significant decrease in area in land use in the downstream area of ​​the Bila watershed was Forest covering an area of ​​125,623 ha, Vacant Land covering an area of ​​103,991 ha, Tegalang Fields covering an area of ​​1809,481 ha, Shrubs covering an area of ​​594,523 ha.